(3EUdGM GdNdd aj TQM CHjGJ GdLeds - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s; (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B377 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi YdefG eGde fcf fYde , haVdfG Ydi cKjQ ef Ndbg hbOe s
(3BNQgG (B:s
(3hde jPcQ Gfg ddaQROb , hde CLO gPG GdHjJ ajeG WdYJ ef TYQ GdaQROb aCeJf efg Ydi MbjbI hgPG eG hLO ef TQM CHjGJ GdLed s
(3HChdgG agQS ddehVhYGJs
(3cJHJ GdYfGhjf HGdMeQIs
(3HBNQgG SeGY Ydi MhGTjgG JYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs